The Impact of Glucagon-Like Peptide 1 Receptor Agonists on Bone Metabolism and Its Possible Mechanisms in Osteoporosis Treatment - Xie, Baocheng; Chen, Shichun; Xu, Yongxiang; Han, Weichao; Hu, Runkai; Chen, Minyi; Zhang, Yusheng; Ding, Shaobo (Frontiers in Pharmacology, 2021)
Diabetes mellitus and osteoporosis are closely related and have complex influencing factors. The impact of anti-diabetic drugs on bone metabolism has received more and more attention. Type 2 diabetes mellitus (T2DM) would lead to bone fragility, high risk of fracture, poor bone repair and other bone-related diseases. Furthermore, hypoglycemic drugs used to treat T2DM may have notable detrimental effects on bones. Thus, the clinically therapeutic strategy for T2DM should not only effectively control the patient’s glucose levels, but also minimize the complications of bone metabolism diseases. Glucagon-like peptide-1 receptor agonists (GLP-1RAs) are novel and promising drug for the treatment of T2DM. Some studies have found that GLP-1RAs may play an anti-osteoporotic effect by controlling blood sugar levels, promoting bone formation and inhibiting bone resorption. However, in clinical practice, the specific effects of GLP-1RA on fracture risk and osteoporosis have not been clearly defined and evidenced. This review summarizes the current research findings by which GLP-1RAs treatment of diabetic osteoporosis, postmenopausal osteoporosis and glucocorticoid-induced osteoporosis and describes possible mechanisms, such as GLP-1R/MAPK signaling pathway, GLP-1R/PI3K/AKT signaling pathway and Wnt/β-catenin pathway, that are associated with GLP-1RAs and osteoporosis. The specific role and related mechanisms of GLP-1RAs in the bone metabolism of patients with different types of osteoporosis need to be further explored and clarified.